Qualitative Study to Explore Potential Directions for Improvements of Fruit and Vegetable Supply Chain Management: A Case Study of Malaysian Agrifood Corporation - Lukmanov, Arman (2010)
The research was carried out to investigate the current supply chain management system of Malaysian Agrifood Corporation (MAFC) and recommend further potential directions of improvements of the supply chain management in terms of increasing its effectiveness and efficiency and keeping up with emerging trends and innovations which can be applied to the Malaysian food industry. MAFC is a Malaysian supply chain management company with integrated supply of fresh fruits and vegetables that are sourced from owned and contracted farms and the spot market in many regions of Malaysia and India and delivered to retailers within Malaysia and to distributors around the world. The company was established in 2006 as a private establishment but government linked establishment. One of the major objectives of the company is to contribute to Malaysian food industry with its recent innovations, advanced practices and technologies in order to increase the competitiveness of the entire industry not only within Malaysia but also globally. MAFC has adopted the controlled environment technology for growing fruits and vegetables and set a system of product supply to Malaysian and foreign customers. According to the CEO of MAFC, the management of the company is motivated to improve the current management processes. Accordingly, this research is based on a proposition that there might be a room for improvements for the current supply chain management system of the company. To achieve the research objectives, a single case study was conducted and the key managers of the supply chain were interviewed. First of all, the current supply chain management system of MAFC is studied. Secondly, the research identifies what recent innovations and advanced practices can be applied to the food supply chain that are shown through a broad literature review and which have been implemented by the members of the supply chain. Finally, a set of recommendations that can improve the fruits and vegetables supply chain management of the company so that it can increase its effectiveness and efficiency and also reviewing the emerging trends, innovations and advanced practices a more viable system is developed. The research describes and analyzes the current supply chain management of the company in terms of structure, processes, management components and supply chain resources. Also, it shows that there are a number of innovations and advance practices in the supply chain management domain available in literature and most of them can be applied to Malaysian food supply chain practices. Some of the identified advanced practices have already been implemented by MAFC and some of them are supposed to be adopted in order to increase the profitability and effectiveness of the MAFC’s supply chain. The findings indicate that Malaysian fresh fruits and vegetables industry is developing and it reacts to the emerging trends and innovations quite dynamically. But despite these factors, there is still some room for improvements in the supply chain system. So, the research shows the further directions of improvements of Malaysian fresh fruits and vegetables supply chain management system as any supply chain activities need continuous improvements and change.